THE INFLUENCE OF PSYCHOLOGICAL ASPECTS ON STUDENT SUCCESS IN THE INDONESIAN MEDICAL DOCTOR NATIONAL COMPETENCY EXAMINATION (UKMPPD) AT A MEDICAL FACULTY - Meida, Nur Shani; Puspitosari, Warih Andan; Majdawati, Ana; Rizqi, Muhammad Arif (Universitas Gadjah Mada, 2023)
Background: The success of medical professional education can be measured by The Indonesian Medical Profession Program Student Competency Test (in Indonesia known as UKMPPD). UKMPPD can also be used as an indicator of clinical year students’ success in achieving competence based on the Indonesian Doctor Competency Standards (known as SKDI). The UKMPPD exam involve the cognitive domain, measured by the computer-Based Academic Test (CBT) and the psychomotor domain, measure by the Objective Structured Clinical Examination (OSCE). There are several factors that can affect students’ success in UKMPPD, one of which is psychological factors namely optimism, motivation, anxiety, depression and fighting spirit.Aims: This study aimed to measure the influence of psychological aspects on students’ success in UKMPPD at the Doctor Professional Education Program (PSPD), Universitas Muhammadiyah Yogyakarta (UMY).Case Discussion: This was an analytic observational with a cross-sectional design. It was conducted at PSPD UMY in 2018. There were 192 students of Universitas Muhammadiyah Yogyakarta (UMY) who underwent the UKMPPD exam in the August 2018 period, became the samples, aged 20-26 years. Students filled out standardized instruments (assessed optimism, motivation, depression, anxiety, fighting spirit).Conclusion: It can be concluded that there is an influence of psychological aspects (optimism, motivation, depression, and anxiety scores) on UKMPPD pass.